2011
DOI: 10.1149/1.3530845
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Traps in the Transition Region at the HfO[sub 2]∕SiO[sub x] Interface by Thermally Stimulated Currents

Abstract: Thermally stimulated currents ͑TSCs͒ have been measured to investigate electron traps in HfO 2 prepared by reactive sputtering on silicon. Broken planes of the silicon crystal, which may contribute to the occurrence of interface states, were identified between the silicon and SiO x interlayer by transmission electron microscopy ͑TEM͒. A second domain was found between SiO x and HfO 2 constituting a gradual transition region between the two oxides. This interface region was found to be a source of unstable char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…52 The tunneling process thus likely involves some kind of trap-assisted tunneling (TAT) mechanism, which, given the fact that a post-deposition anneal is required to activate a large negative charge density, might be thermally induced. 53,54 Nevertheless, assuming that the tunneling process can be described by a direct-tunneling-like mechanism, the charge density at the SiO 2 /Al 2 O 3 interface can be written as…”
Section: Dependence Of the Effective Charge Density On The Interlamentioning
confidence: 99%
“…52 The tunneling process thus likely involves some kind of trap-assisted tunneling (TAT) mechanism, which, given the fact that a post-deposition anneal is required to activate a large negative charge density, might be thermally induced. 53,54 Nevertheless, assuming that the tunneling process can be described by a direct-tunneling-like mechanism, the charge density at the SiO 2 /Al 2 O 3 interface can be written as…”
Section: Dependence Of the Effective Charge Density On The Interlamentioning
confidence: 99%
“…5 (b) from consecutive measurements on the same sample. Repeated measurements gave rise to peak positions at various temperatures, suggesting structural instabilities of these traps thus changing their energy positions and emission properties [31]. The solid TSC curves in this diagram are theoretical while the measured data coincide only up to a certain temperature, where the signal collapses.…”
Section: Traps In High-k/sio X Transitions Regionsmentioning
confidence: 88%
“…In this transition region, a high concentration of traps is expected. For the HfO 2 /SiO x stack, it was recently demonstrated that these traps are structurally unstable and communicate with the free carriers in the silicon crystal by a combined thermal-tunneling process [30,31].…”
Section: Traps In High-k/sio X Transitions Regionsmentioning
confidence: 99%
See 2 more Smart Citations